Systematic Literature Review on Smoothed Particle Hydrodynamic Method for Coastal Protection Optimizing - Reynaldi Javier Purba; Ramadhani Ramadhani; Kemal Hamdani (Syntax Idea)
The Smoothed Particle Hydrodynamic (SPH) method has been extensively used in coastal engineering applications, including coastal protection optimization. This paper presents a systematic literature review of research studies that have utilized SPH method for coastal protection optimization. The review covers various applications of SPH method, such as optimizing breakwaters, studying wave-structure interactions, modelling wave-induced erosion, simulating tsunami run-up and inundation, and optimizing artificial reefs. The review demonstrates the versatility of SPH method in coastal engineering applications and highlights the importance of its capabilities in simulating complex coastal processes. The limitations and challenges of using SPH method are also discussed in the context of coastal protection optimization. The review provides a comprehensive overview of the current state of research on SPH method for coastal protection optimization, which can serve as a valuable reference for researchers and practitioners in the field